BEDESTENS FROM OTTOMAN PERIOD: FACTORS OF INFLUENCE IMPLEMENTED IN CONTEMPORARY CITY CONCEPT - Namicev, Petar (Journal of process management and new technologies, 2016)
Bedesten or covered marked, are usualy located in the bazaar area of the Balkan city type. Bedesten was served as a place for the transactions of valuable goods, quality fabrics and the shops with luxury items in the past. The analysis of factors are presented at three characteristic preserved bedestens in Bitola, Skopje and Shtip, dating from XV-XVI century.Through presented factors  were investigated the impacts of re-building and conservation interventions on the activity of objects in modern urban context, the role of the local community, which affects at the development of cultural tourism,at theambiental values of the environment, raising awareness, identifying and attitude of the population to the monuments.The identification of factors which affecting the modern treatment of historic buildings is important because of their adequate treatment adapted to modern needs, raising of awareness of population and development of cultural tourism.